Analisis Sentimen Opini Publik Terhadap Undang-Undang Cipta Kerja pada Twitter Menggunakan Metode Naive Bayes Classifier - Yanuar Nurdiansyah; Fatchur Rahman; Priza Pandunata (Akademi Angkatan Udara, 2021)
Sentiment analysis or Opinion Mining is a way of solving a problem based on public opinion that is widely circulated on social media which is expressed in text form. Sentiment analysis is very helpful for the government / an agency in knowing public opinion about a policy that has just been issued without using conventional survey methods. The sentiment analysis carried out focuses on trending tweet topics on Twitter with trending topics on October 5 to 10 are #Omnibuslaw, #tolakruuciptakerja, #UUCiptaKerja, and #tolakomnibuslaw, and the trending topic on November 21 and 22 is